Efficacy of nasal bridles in avoiding percutaneous endoscopic gastrostomy placement. Issue 2 (13th March 2012) - Webb, Gwilym; Gupta, Prakash; Fitchett, Jo; Simmons, Jon; De Silva, Aminda
Abstract : Objective: The aim of the study was to report the use of nasogastric tube bridles to avoid dislodging of percutaneous endoscopic gastrostomy tubes. Specifically it was intended to see if they reduced feeding time, medical input and costs. Design: and setting This was a cohort study in a district hospital setting. Patients: 164 patients admitted with conditions causing acutely impaired swallowing. Interventions: 140 of 164 patients referred received a NGT bridle. Results: Of these, 49 (35%) died by 28 days and 68 (48.6%) at 1 year; 73 (52.1%) had regained adequate oral intake at 28 days and 27 (19.2%) had proceeded to PEG. Of those not bridled, nine (37.5%) died by 28 days and 10 (41.7%) at 1 year with the remainder eating. There was no significant difference in mortality between groups. There were no complications attributed to bridles. Conclusion: We conclude that nasogastric bridles are safe and represent an appropriate method to maintain nutrition while seeing if the underlying disease process will stabilise in these critically ill patients. They have the benefits of avoiding unnecessary PEG and the associated complications and cost.